The UPAYA STRATEGI PEMASARAN MENGGUNAKAN PENINGKATAN NILAI JUAL JASA PENDIDIKAN: Marketing - Prayitno, Dedi (PRIMA EKONOMIKA, 2023)
The marketing strategy for higher education services in Indonesia, especially in Yogyakarta, now has many challenges. Marketing of educational services is a strategy to increase the selling value of the Academy which is an important element for the quality and progress of the educational level of educational institutions. This scientific article specifically discusses the strategy of higher education in increasing the selling value of the Academy, as well as how to apply the marketing strategy for educational services in increasing the selling value of the "YAB" Academy of Physiotherapy. The author critically examines how the widespread marketing of educational services departs from the initial concept of the Academy as an educational service provider in the health sector and not as a business area in the world of education. The academy as an education service provider needs to learn and have a passion for increasing customer satisfaction because education is a continuous teaching and learning process. Marketing of educational services at the Academy does not mean commercialization, but prioritizes quality education and provides excellent service to stakeholders. Satisfaction with the community which can be useful in increasing the selling point of the Academy